SISTEM INFORMASI PERMINTAAN PRODUK BARU BERBASIS WEB PADA DEPARTEMEN ENGINEERING DI PT LEOCO INDONESIA - Intan Sari Rahayu; Gatot Tri Pranoto; Wahyu Hadikristanto (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
In the process of submitting new products from customers, they often experience process inefficiencies, especially in proposing product samples. In a manual system, many use forms whose steps can result in the process of making new products inefficient. A web-based new product request information system is an application that is used to facilitate the process of submitting and managing requests for new products in the Engineering department of PT. Leoco Indonesia. This system is designed to facilitate communication between the Engineering team and other departments, as well as speed up and increase the efficiency of the new product request process. In this study the authors formulate how to design a system that can overcome problems in the process of submitting requests for new product samples Engineering Department PT. Leoco Indonesia is web-based which can support and be integrated especially in the Engineering Department which can reduce the risks of errors and can speed up the flow of data activity.